Systematic Literature Review: The Influence of Divorce on Economic Resilience Single Mother Families - Turmudi, Muhamad; Tarihoran, Nafan; Aspandi, Aspandi (Institut Agama Islam Negeri Kendari, 2025)
Divorce affects the economic resilience of families, especially for single mothers. Single mothers have to play a dual role as breadwinners and take care of their children without the help of their ex-husband. This research aims to analyze the effect of divorce on economic resilience and efforts to maintain the economic resilience of single mother families after divorce. The method used in this research is a systematic literature review based on big data of 600 research articles published between 2019-2024 via publish or perish Crossref, Google Scholar and OpenAlex with VOSviewer visualization. The articles used to analyze the problems in this research were 13 articles based on keyword criteria that represented the research problem. From the thirteen articles used in the systematic literature review, it was found that divorce had a negative effect on the financial condition of single mothers who had limited resources, did not have a permanent job or during their household ties depended on the results of their husband's work. Single mothers face many difficulties because they have to do everything alone at home, including meeting the daily needs of themselves and their children. Single mothers make various efforts to maintain the family's economic resilience through economic activities in the form of selling goods or services, working as company employees, laborers, household assistants and even becoming migrant workers